STUDI JOB BURNOUT PADA PERSONIL SATUAN TUGAS LALU LINTAS DI TINGKAT POLDA - Prayudha Dharma; Retno Kusumastuti Hardjono (Journal Publicuho, 2025)
A task force is an additional duty imposed on traffic personnel with density and workload that exceeds routine duties in maintaining security, order, and traffic flow in certain important situations. Serious attention to this issue is needed to anticipate job burnout that can potentially damage the quality of service and personnel actions to society that impact on institutional reputation. Therefore, this study aims to examine and analyse various factors that affect job burnout, such as job stress, leader-member exchange (LMX), and co-worker support. As many as 89 personnel participate in the term to respond to proposed G-form questionnaires. Then, the data was analysed through Smart-PLS Software and the Two-Stage calculation method to test the moderating effects of co-worker support. The result shows that the direct effect of job stress significantly affects job burnout, but that effect could be weakened strongly by the moderating effect of co-worker support. Further, LMX also has a significant direct effect on job burnout, but the moderating effect of co-worker support on those relationships could substitute for the effect of LMX on job burnout.